Gibbs, Philip. The Word in the Third World, Divine Revelation in the Theology of Jean-Marc Ela, Aloysius Pieris and Gustavo Gutiérrez. - Madangi Sengi, Jean de Dieu ('Ilu. Revista de Ciencias de las Religiones, 1998)
Sin resumen